(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The main aim of the study was to isolate and identify the bacterial agent and to determine the susceptibility pattern of isolates to different antibiotics. Methods: This retrospective study was conducted from February to October 2015 in microbiology laboratory of All Nepal Hospital Kathmandu, Nepal. The clinical specimens were processed for isolation and identification of bacteria following standard microbiological procedures. Antibiotic susceptibility pattern of isolates were determined according to CLSI guidelines (CLSI 2014) Results: A total of 271 clinical specimens were processed where 164 (60.5%) showed growth positivity. A total 164 bacterial isolates were detected among which 84 (51.22%) were Gram positive 80 (48.78%) were Gram negative bacteria. Thirteen different species of bacteria were isolated. The most prevalent isolate was Staphylococcus aureus 53 (32.30%) followed by E. coli 34 (20.80%), (CoNS) 15 (9.10%), Klebsiella pneumoniae 15 (9.10%), Enterococcus fecalis 12(7.30%), Pseudomonas aeruginosa 10 (6.10%), Acinetobacter spp. 7 (4.30%) Citrobacter spp., Proteus spp., Klebsiella oxytoca were less common. S. aureus was most susceptible to Amikacin. Vancomycin was the most effective drugs for Enterococcus fecalis. Among Gram negative bacteria E. coli was found most sensitive to Polymyxin B (100%) and Imipenem (76.5%) where Pseudomonas aeruginosa was sensitive to, Amikacin, Imipenem (80%). Polymyxin B was the most effective drugs for Klebsiella pneumoniae. Acinetobacter spp. was found highly resistant to different antibiotics. Conclusion: Antibiotic susceptibility evaluation showed Aminoglycosides, Phenicols Polymyxin, and Imipenem was the most effective drugs overall.